Actualización diagnóstica y terapéutica de la enfermedad de Still - Porras Villacis, Erik Stalin (2023)
ABSTRAC Still's disease is a disease that occurs in about 1.5 people per million inhabitants. It is characterized by the presence of an acute febrile picture accompanied by articular and extra-articular manifestations that can generate local and systemic damage that can endanger the lives of patients. The objective of this research was to carry out a diagnostic and therapeutic update of Still's disease. For this, a basic, descriptive and cross-sectional investigation was carried out consisting of a bibliographic review of documents published in the last 5 years. A total of 101 documents were identified, of which 26 were used in the study. The information was obtained from regional (Latindex, Lilacs, Scielo, and Redalyc) and high-impact databases (Scopus, Medline, PubMed, and Ice Web of Science). The main results include the description of the clinical characteristics of the disease, the elements that confirm the clinical suspicion and the definitive diagnosis of the disease, as well as its therapeutic elements. A diagnostic and therapeutic algorithm was designed for the management of the disease. It is concluded that, despite being considered a rare disease, its presence increases the risk of complications, functional disability and affectation of the perception of health-related quality of life. Updating the knowledge about the diagnostic and therapeutic elements allows an early diagnosis and adequate treatment of the disease. Keywords: Autoimmunity; rheumatic disease; Still's disease; Immune system